Utilizing phase-shifted long-period fiber grating to suppress spectral broadening of a high-power fiber MOPA laser system. (15th July 2021) - Bian, Yinxu; Jiao, Kerong; Wu, Xuecheng; Shen, Hua; Yang, Feiyan; Zhu, Rihong
Abstract: Suppressing nonlinear effects in high-power fiber lasers based on fiber gratings has become a hotspot. At present, research is mainly focused on suppressing stimulated Raman scattering in a high-power fiber laser. However, the suppression of spectral broadening, caused by self-phase modulation or four-wave mixing, is still a challenging attribute to the close distance between the broadened laser and signal laser. If using a traditional fiber grating with only one stopband to suppress the spectral broadening, the signal power will be stripped simultaneously. Confronting this challenge, we propose a novel method based on phase-shifted long-period fiber grating (PS-LPFG) to suppress spectral broadening in a high-power fiber master oscillator power amplifier (MOPA) laser system in this paper. A PS-LPFG is designed and fabricated on 10/130 passive fiber utilizing a point-by-point scanning technique. The resonant wavelength of the fabricated PS-LPFG is 1080 nm, the full width at half maximum of the passband is 5.48 nm, and stopband extinction exceeds 90%. To evaluate the performance of the PS-LPFG, the grating is inserted into the seed of a kilowatt-level continuous-wave MOPA system. Experiment results show that the 30 dB linewidth of the output spectrum is narrowed by approximately 37.97%, providing an effective and flexible way for optimizing the output linewidth of high-power fiber MOPA laser systems.